2020
DOI: 10.1136/neurintsurg-2020-017053
|View full text |Cite
|
Sign up to set email alerts
|

International teleproctoring in neurointerventional surgery and its potential impact on clinical trials in the era of COVID-19: legal and technical considerations

Abstract: BackgroundExisting travel restrictions limit the mobility of proctors, significantly delaying clinical trials and the introduction of new neurointerventional devices. We aim to describe in detail technical and legal considerations regarding international teleproctoring, a tool that could waive the need for in-person supervision during procedures.MethodsInternational teleproctoring was chosen to provide remote supervision during the first three intracranial aneurysm treatments with a new flow diverter (currentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
(21 reference statements)
0
5
0
4
Order By: Relevance
“…Using this system, trainees can learn the endovascular cutting-edge technique using their own monitoring system, such as the iPad. A similar system was reported by Orru et al [6] for endovascular proctoring purposes in the United States and Canada. In their system, images were controlled by the operator site, not the proctor site.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Using this system, trainees can learn the endovascular cutting-edge technique using their own monitoring system, such as the iPad. A similar system was reported by Orru et al [6] for endovascular proctoring purposes in the United States and Canada. In their system, images were controlled by the operator site, not the proctor site.…”
Section: Discussionmentioning
confidence: 70%
“…A similar system was reported by Orru et al . [ 6 ] for endovascular proctoring purposes in the United States and Canada. In their system, images were controlled by the operator site, not the proctor site.…”
Section: Discussionmentioning
confidence: 99%
“…A welcome derivative of our sequestration was the development of virtual meeting platforms and telemedical outreach to our patients. As we gradually emerge from the pandemic and re-emerge into personal interaction, these virtual venues remain important mechanisms to promote global medical participation and enhance patient care 5. Virtual interaction also allows investigators to continue scientific trials, while also facilitating access to novel devices and techniques 6.…”
mentioning
confidence: 99%
“…Virtual interaction also allows investigators to continue scientific trials, while also facilitating access to novel devices and techniques 6. Global teleproctoring initiatives could potentially enable neurointerventionalists in remote areas with limited resources to perform complex cases and use novel technology under live supervision 5. Similarly, the advent of robotic neurointervention offers the tantalizing prospect of performing procedures remotely 7.…”
mentioning
confidence: 99%
“…Several groups assessed the feasibility of teleproctoring and its impact on various elements of practice, including clinical trials. 19 Telehealth had been a challenging area historically for a variety of reasons, including reimbursement. The pandemic accelerated trends and Lun et al found that virtual clinics were preferred by patients and physicians alike for non-urgent follow-up appointments.…”
mentioning
confidence: 99%